The Impact of Service Quality and Trust on the Satisfaction of Muzakki at the Amil Zakat Institution Baznas in Makassar City - Samsul Rizal; Buyung Romadhoni; Irwan Abdullah; Hariyati Hariyati (Universitas Muhammadiyah Makassar, 2023)
This research employs a quantitative approach with the objective of assessing the influence of service quality and trust on the satisfaction of Muzakki at the Amil Zakat Institution BAZNAS in Makassar City. The sample for this study was drawn from the BAZNAS office in Makassar City. The data utilized in this research is quantitative in nature, collected through distributed questionnaires that pertain to the focal points of the study. Data collection encompassed the observation and distribution of questionnaires to a sample of 35 respondents. In this study, the data collection process drew upon both primary and secondary data sources. The research instrument implemented for data collection was based on the Likert scale method. The data analysis technique employed is the multiple linear regression test. The results of the data analysis, conducted using statistical calculations via the Statistical Package for the Social Sciences (SPSS) version 22 application, reveal a significant positive relationship between service quality, trust, and satisfaction at the Amil Zakat Institution BAZNAS in Makassar City. This study highlights the pivotal conclusion that service quality and trust hold a substantial positive impact on the satisfaction levels of Muzakki at the Amil Zakat Institution BAZNAS in Makassar City. Notably, the provision of high-quality service significantly contributes to shaping the institution's image, consequently fostering enhanced trust among individuals, leading to a heightened willingness to recommend the services to others.